Does immigration affect wages? A look at occupation-level evidence - Pia M. Orrenius; Madeline Zavodny (Institute for the Study of Labor (IZA), 2006)
Previous research has reached mixed conclusions about the effect of higher levels of immigration on the wages of natives. This paper reexamines this question using data from the Current Population Survey and the Immigration and Naturalization Service and focuses on differential effects by skill level. Using occupation as a proxy for skill, we find that an increase in the fraction of foreign-born workers tends to lower the wages of natives in blue collar occupations particularly after controlling for endogeneity but does not have a statistically significant negative effect among natives in skilled occupations. The results also indicate that immigrants adjusting their immigration status within the U.S., but not newly arriving immigrants, have a significant negative impact on the wages of low-skilled natives. This suggests that immigrants become closer substitutes for natives as they spend more time in the U.S.
urn:nbn:de:101:1-2008051385
Keywords: 330